Students' mathematical representation ability in terms of field dependent and field independent cognitive styles of Quadrilateral Flat material - Nasrullah, Nasrullah (SAINTIS Publishing, 2023)
Eld-independent cognitive styles in solving problems on rectangular shape material. This type of research is descriptive qualitative research, namely by interpreting data with the stages of image analysis, interviews, observation, and documentation. The subject of this study was taken by purposive sampling after carrying out the GEFT test in class V where 4 samples were taken based on field dependent and field independent cognitive styles. The instruments prepared in this study were GEFT test questions and mathematical representation questions. From the results of this study it shows that: 1) students who have a field dependent cognitive style carry out mathematical representations visually students are not always able to make pictures and symbols of a problem and in mathematical expression students can make mathematical models and can perform calculations according to what has been taught by the teacher accurately or always think globally without making new discoveries and in written expression students are less able to make solutions in logical and systematic written words. 2) students who have a field independent cognitive style make mathematical representations in solving problems with visualization stages can understand the problem and change it in the form of images and symbols in accordance with the problems that are understood and in mathematical expression students and can make plans for solving with mathematical models and can carry out calculations in their own way in accordance with their experience which is considered fast average in written expression students are able to express solutions in written words in a systematic and logical manner.